The UN Role in the Sphere of International Legal Regulation of Small Arms and Light Weapons - Y. N. Maleev; i. B. Serov (Московский журнал международного права, 2017)
There is no global regime of Non-Proliferation of Small Arms and light weapons. A lot of international organizations, UNO – is most active among them, try to regulate this sphere. In 2001 UNO adopted the United Nations Programme of Action on Small Arms and Light Weapons, which, among all, presupposes regular observations of its implementation. (The last one was made in 2016). In 2013 the UN General Assembly adopted the Arms Trade Treaty (ATT)10, which is signed by 130 states and ratified by 91. Russia now considers it be inappropriate to sign the ATT. Among some other sources of international law in this question the Wassenaar Arrangements of 1996 are, perhaps, the first to be mentioned. The UN sanctions decisions (embargo) in this sphere ere not the kind of international liability but the measures of compulsion with the aim of restorationof the disturbed peace order. But the UN embargos on the arms supply are not effective. Historically beginning from 1800 to introduce embargo on the territory of Russia is prerogative of the first person of the state. In the Russian Federation now that is the President of the state. The activity of terroristic organizations is not under the mercy of political and diplomatic instruments of peace keeping. So the important task of international policy is the control on manufacture and proliferation of military aimed production.